2022
DOI: 10.1186/s12891-022-05681-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the expression pattern and diagnostic value of PPARγ in malignant and benign primary bone tumors

Abstract: Purpose The quantifiable description of PPARγ expression pattern beside mechanistic in-vitro evidence will provide insights into the involvement of this mediator in tumor pathogenesis. This study is focused on illuminating the PPARγ gene and protein expression pattern, its association with tumor deterioration and its diagnostic value in different types of primary bone tumors. Methods The expression pattern of PPARγ was investigated in the 180 bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The PPAR family members are ligand-activated transcription factors with three isotypes, PPAR α, γ, and δ. PPARγ plays a crucial role in glucose metabolism, fatty acid oxidation, cell cycle regulation, adipocyte differentiation, lipid storage, and inflammation [ 13 ]. The exact role of PPARγ in tumors as oncogenic versus tumor suppressive remains controversial [ 23 ]. PPARγ association with neoplastic pathogenesis has recently been increasingly recognized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PPAR family members are ligand-activated transcription factors with three isotypes, PPAR α, γ, and δ. PPARγ plays a crucial role in glucose metabolism, fatty acid oxidation, cell cycle regulation, adipocyte differentiation, lipid storage, and inflammation [ 13 ]. The exact role of PPARγ in tumors as oncogenic versus tumor suppressive remains controversial [ 23 ]. PPARγ association with neoplastic pathogenesis has recently been increasingly recognized.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our results, another study reported that induced PPARγ upregulation is associated with wide TGCT tumor necrosis [ 15 ]. The differences in reported results can be explained by the varying role of PPARγ depending on varying tumors, individual characters, and PPARγ concentration [ 23 ]. Moreover, although PPARγ is a nuclear receptor transcription factor, different subcellular locations of IHC expression were described in the literature and were associated with different neoplastic features and prognoses [ 13 , 23 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-CD44v6 antibody (Catalog number: ab217902; Abcam) with the dilution of 1:500 and anti-mouse IgG HRP-conjugated secondary antibody (Catalog number: ab6728; Abcam) was applied for staining and detection. The detail of the protocol and analysis is based on the protocol described in our previous study [ 27 , 28 ]. Briefly, tissue blocks were prepared in optimal cutting temperature (OCT) embedding medium and fixed in paraformaldehyde (4%).…”
Section: Methodsmentioning
confidence: 99%
“…The non-specific antigenic sites on tissue sections were blocked using goat serum (10%) and the intensity of staining was visualized using horseradish peroxidase activity and chromogens. The percentages of CD44v6 intensity for each sample were measured using Image J software [ 28 ] and presented as graphs (Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%